A Comparison of Growth on Mercuric Chloride for Three Lemnaceae Species Reveals Differences in Growth Dynamics That Effect Their Suitability for Use in Either Monitoring or Remediating Ecosystems Contaminated With Mercury - Yang, Jingjing; Li, Gaojie; Bishopp, Anthony; Heenatigala, P. P. M.; Hu, Shiqi; Chen, Yan; Wu, Zhigang; Kumar, Sunjeet; Duan, Pengfei; Yao, Lunguang; Hou, Hongwei (Frontiers in Chemistry, 2018)
Mercury (Hg) is a toxic heavy metal that can alter the ecological balance when it contaminates aquatic ecosystems. Previously, researchers have used various Lemnaceae species either to monitor and/or remove heavy metals from freshwater systems. As Hg contamination is a pressing issue for aquatic systems worldwide, we assessed its impact on the growth of three commonly species of Lemnaceae - Lemna gibba 6745, Lemna minor 6580 and Spirodela polyrhiza 5543. We exposed plants to different concentrations of mercuric chloride (HgCl2) and monitored their growth, including relative growth rate, frond number, and fresh weight. These data were coupled with measurements of starch content, levels of photosynthetic pigment and the activities of antioxidant substances. The growth of all three lines showed significant negative correlations with Hg concentrations, and starch content, photosynthetic pigment, soluble protein and antioxidant enzymes levels were all clearly affected. Our results indicate that the L. gibba line used in this study was the most suitable of the three for biomonitoring of water contaminated with Hg. Accumulation of Hg was highest in the S. polyrhiza line with a bioconcentration factor over 1000, making this line the most suitable of the three tested for use in an Hg bioremediation system.